Sistem Informasi Penjualan Pupuk Bersubsidi Dan Nonsubsidi Berbasis Web - Permatasari, Laras; Suhari, Yohanes (STIKOM Tunas Bangsa Pematangsiantar, 2023)
PT. Pupuk Sriwidjaja Palembang Sales of PSO Central Java 1 has a Pusri Mart which sells retail non-subsidized fertilizers. The fertilizer sales system at Pusri Mart is still ordinary and simple, where buyers have to go to a shop to buy fertilizer. As a result, the range of non-subsidized fertilizer sales at Pusri Mart is still limited. To support the company's progress, a web-based sales information system will be developed using the SDLC method, so that it can be used to carry out fertilizer purchase transactions at Pusri Mart based on a website that can be accessed anytime and anywhere. Where can expand sales and help customers complete purchases more easily and in less time. The fertilizer sales information system includes an order subsystem, a proof of payment reporting subsystem.